The angle A is such that secA+tanA=2
show that secA - tanA=1/2 and hence find exact value of cos A
sec² A = 1 + tan² A
sec² A - tan² A = 1
(sec A + tan A)(sec A - tan A) = 1
(2) (sec A - tan A) = 1
secA - tanA=1/2 (shown)
secA - tanA + secA+tanA = 2.5
sec A = 1.25
cos A = 0.8 = 36.9 degrees
ok thanks,
Some more questions
(a) Prove identity cot(1/2)A - tan (1/2)A= 2cotA
**i have attempted it **
1/ tan(1/2)A - tan(1/2)A=(1 – tan2(A/2)) / (tanA/2)
If tan2A=(2tanA) / 1-tan2A ----(1)
Let A = A/2
tan A = ( 2tan(A/2) ) / (1 – tan2(A/2))
1 – tan2(A/2) = ( 2tan(A/2) ) / (tan A ) ----(2)
from (2)
(1 – tan2(A/2)) / (tanA/2) = ( 2tan(A/2) ) / (tanA/2) (tan A ) = 2 / tanA
1 / tanA =cot A
Therefore, cot(1/2)A - tan (1/2)A= 2cotA
**is this correct way, is there any easier way??**
(b)By choosing suitable numerical value for A show that tan 15 is a root of quadratic equation t^2 + (2√3)t - 1 =0
**how to do this??**
Hi,
For the proof, a faster way is to express cot and tan in terms of sin and cos, i.e.
(cos A/2) / (sin A/2) - (sin A/2) / (cos A/2)
= [ cos^2 A/2 - sin^2 A/2 ] / [ sin A/2 cos A/2 ]
= cos A / [ 1/2 sin A ]
= 2 cot A (shown)
Let A = 15 deg, since we know that tan 30 deg = 1/sqrt(3). Then we obtain
cot 15 - tan 15 = 2 cot 30
1 / (tan 15) - tan 15 = 2 sqrt(3)
Multiplying both sides by tan 15, we obtain
1 - tan^2 15 = 2 sqrt(3) (tan 15)
Rearranging, we have tan^2 15 + (2 sqrt(3)) (tan 15) - 1 = 0, of which we see that t = tan 15 is a root to the said quadratic equation.
Thanks!
Cheers,
Wen Shih